2019
DOI: 10.1523/eneuro.0284-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Eye Contact Special? Neural Substrates of On-Line Mutual Eye-Gaze: A Hyperscanning fMRI Study

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 109 publications
(141 reference statements)
1
58
1
Order By: Relevance
“…Since the last decade of the twentieth century, fMRI has become FIGURE 1 | Neuroimaging methods used in Hyperscanning. (A) From Koike et al (2019). View of the dual fMRI facility used to study mutual gaze.…”
Section: Type Of Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the last decade of the twentieth century, fMRI has become FIGURE 1 | Neuroimaging methods used in Hyperscanning. (A) From Koike et al (2019). View of the dual fMRI facility used to study mutual gaze.…”
Section: Type Of Methodsmentioning
confidence: 99%
“…To tackle the problem that occurs when two scanners are required to complete a study, King-Casas (2005) conducted a study using scanners in Texas and California linked via the Internet. Afterward, other studies were performed in facilities that possessed two scanners; however, until now, only a few studies have tried to investigate social interaction with the fMRI hyperscanning method (Tomlin, 2006;Saito et al, 2010;Schippers et al, 2010;Tanabe et al, 2012;Tomlin et al, 2013;Spiegelhalder et al, 2014;Koike et al, 2016Koike et al, , 2019Abe et al, 2019). One reason for that might be difficulty in creating experimental paradigms that involve interaction between participants without movement and communication.…”
Section: Type Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Touch is the most effective intervention for activating positive biological markers of connection . However, brief bouts of undivided, direct, and reciprocal eye contact, even done remotely, can be as effective at mobilizing biological connection responses in the brain. This research has important implications not only for how we raise children but how we support and provide care to older adults.…”
Section: Social Distancing Vs Social Isolation: Connection As a Biolomentioning
confidence: 99%
“…The results revealed that the perception of power changes depending on the emotional response of one's partner. A previous fMRI study has measured the brain activity of two individuals during face-to-face interactions and observed interindividual synchronized activity in the lateral occipitotemporal cortex (Koike et al, 2019).…”
Section: Other Dynamic Aspects Of Emotional Communicationmentioning
confidence: 99%